Initial Value Compensation Using Additional Input for Semi-Closed Control Systems - Hirose, N.; Iwasaki, M.; Kawafuku, M.; Hirai, H. (IEEE transactions on industrial electronics (1982), 2009)
This paper presents a novel initial value compensation (IVC) using an additional input for semi-closed control systems. The authors have already proposed the IVC approach using the additional input for residual vibration suppression in the fast and precise positioning control. In the approach, however, an essential subject has remained, i.e., the positioning control in the load side could not satisfy the required performance because the systems have been constructed under the assumption of a semi-closed control system. An improvement of the control performance in load position, therefore, is discussed in this paper, where the appropriate assignments of poles and zeros in IVC are ensured, considering the transfer functions of position in both sensor and load for the control initial values. The effectiveness of the proposed approach has been verified by numerical simulations and experiments using a prototype.